Toward a better understanding of the relationship between influenza vaccine efficacy against specific and non-specific endpoints and vaccine efficacy against influenza infection (Epidemiology, Biostatistics, and Public Health, 2022)
In influenza vaccination studies assessing vaccine efficacy (VE), both specific and non-specific endpoints (outcomes) are used. We present a formula for the relationship between VE against influenza-related outcomes (VEO), specific and non-specific, and that against influenza infection (VEI). In its simplest form, the formula comprises two additional parameters: the influenza attack rate among unvaccinated subjects, and the relative risk of the outcome for influenza infected subjects versus non-infected subjects. Both parameters may show large between-seasonal variation, which translates to a large between-seasonal variation of  VEO estimates. With the full form of the formula it can be shown that, contrary to popular believe, VEO may be greater than VEI. We argue that interpreting VEO estimates in terms of “low” or “high” is not possible without taking the costs of an outcome case into account. We conclude that the decision to use a non-specific endpoint as surrogate for influenza infection should be taken in the awareness of these limitations.